A review of nutrient, water and organic matter dynamics of tropical acacias on mineral soils for improved management in Southeast Asia. (15th May 2019) - Mendham, D. S.; White, D. A.
ABSTRACT: More than 3 000 000 ha of tropical acacias have been established in recent decades, mostly grown on short rotations of 4–7 years, by a range of growers, from smallholders in Vietnam with less than 5 ha to large industrial growers in Sumatra managing hundreds of thousands of hectares. While the acacia estate is declining in some areas due to disease susceptibility, it is still expanding in other areas, and acacias would probably be the preferred species in many areas if the disease issues can be overcome. To date, many of the silvicultural management practices have largely been based on operational trial and error rather than backed by scientific evidence. To ensure sustained production, a deeper understanding of the mechanism for the response of acacias to management and environment is required. The objective of this paper is to review recent advances in our knowledge of the nutrient, water and organic matter dynamics of acacia plantations on mineral soils in Southeast Asia. We show that water availability is a key factor influencing productivity in many locations, but also that there are options for new approaches to management, including regional and site selection (or choice to plant or not on any given plot of land), and an understanding of nutritional requirements will help managers to adopt best practices in their plantations. While many plantations show significant responses to nutrients, particularly phosphorus (P, e.g. up to 200% stem volume increase at age one year); initial large responses to P fertiliser are reported to diminish over time, such that the response tends to be non-significant at many sites by harvest age. Only small quantities are recommended at establishment (equivalent to around 10 kg P ha −1 ) to maximise productivity. Large quantities of site nutrient pools are held in harvesting debris or slash. Slash should be considered a valuable resource for sustaining productivity into the future, and its role in relation to fertiliser application needs further study.